O processo de ocupação do estado de Rondônia e a desconstrução da identidade Indígena dos Karipuna - Behenck, Ildo Justo (2024)
This study examines the impact of the colonization process in Rondônia on the identity of Indigenous peoples, with special emphasis on the Karipuna group, from the 1970s to the 1990s. The main objective is to understand how colonization has affected the cultural identity of these people. To this end, the specific objectives included analyzing the displacement of Indigenous peoples, identifying the Karipuna, understanding their original culture, and evaluating the consequences of land expropriation and the pressure of economic development on the resignification of their identity. The methodology used was a qualitative approach based on bibliographical and documentary research, using the conceptual framework of the coloniality of power to guide the analysis. The results showed that, despite adversity, the Karipuna have managed to preserve the essential aspects of their cultural identity through a continuous effort of resistance and adaptation. Cultural revitalization initiatives, such as the reintroduction of traditional practices and the strengthening of the native language, have been fundamental to the preservation of their identity. In addition, this research has underscored the importance of public policies that promote the protection of Indigenous rights and the preservation of their cultures. The conclusion is that it is important to preserve cultural diversity and indigenous identity while respecting self-determination and traditional lands.